Relationship Between Metabolic Syndrome and Carotid Intima‐Media Thickness: Cross‐Sectional Comparison Between Psoriasis and Psoriatic Arthritis. Issue 1 (January 2014) - Lin, Yih Chang; Dalal, Deepan; Churton, Sarah; Brennan, Danielle M.; Korman, Neil J.; Kim, Esther S. H.; Husni, M. Elaine
<x xml:space="preserve">Abstract</x> Objective To determine the differences in carotid intima‐media thickness (CIMT) between patients with psoriatic diseases with and without metabolic syndrome. Methods Eligible patients from the Cardiometabolic Outcome Measures in Psoriatic Arthritis Study database, which is comprised of both psoriasis and psoriatic arthritis (PsA) patients enrolled at 2 academic medical centers, were included. Detailed cardiovascular (CV) risk factors, including metabolic syndrome profiles, medication use, disease activity, and CIMT, were examined. Results A total of 343 patients with psoriatic disease were evaluated (42.28% with psoriasis and 57.72% with PsA). PsA patients were significantly older, with longer disease duration and higher blood pressure, body mass index, and C‐reactive protein (CRP) level. PsA patients took more disease‐modifying antirheumatic drugs (DMARDs) and corticosteroids and underwent more CV procedures. There were no differences in prior CV events, family history of CV risk, and Framingham/Adult Treatment Panel III Risk Score. PsA patients had a higher risk of metabolic syndrome (univariate odds ratio [OR] 1.78 [95% confidence interval (95% CI) 1.08–2.95], P = 0.025). Even after adjusting for age, CRP level, and diastolic blood pressure, PsA patients not taking DMARDs were twice as likely to have metabolic syndrome compared to psoriasis patients (adjusted OR 2.09 [95% CI 0.78–5.59], P = 0.049). PsA patients with metabolic syndrome had the thickest CIMT compared to any other group (P < 0.001). Conclusion PsA patients had an increased prevalence of metabolic syndrome with significantly greater CIMT measurements compared to patients with psoriasis. Furthermore, PsA patients with metabolic syndrome had the greatest CIMT measurements compared to PsA patients without metabolic syndrome and psoriasis patients with or without metabolic syndrome. Incremental increases in inflammatory pathways in PsA may contribute to a higher CV risk as compared to psoriasis patients.